Normative Formation of Economic Advantages of Labor Organization in the Federal Territory - V. A. Mayboroda (Теоретическая и прикладная юриспруденция)
In this study, on the basis of a systematic analysis of the regulatory regulation of the features of the organization of public power in the federal territory, in cooperation with special legal regimes of certain types of economic activity, the foundations for the formation of economic advantages of labor organization in certain sectors of the economy are revealed. Accordingly, the very features of the organization of public power determine the regimes of economic activity that allow the rational organization of labor activity, which in itself becomes a distinctive feature of the federal territory, distinguishing it from other special economic regimes (territories of advanced development, special economic zones, etc.).